2013
DOI: 10.1103/physrevlett.110.040404
|View full text |Cite
|
Sign up to set email alerts
|

Pinning of Fermionic Occupation Numbers

Abstract: The Pauli exclusion principle is a constraint on the natural occupation numbers of fermionic states. It has been suspected since at least the 1970s, and only proved very recently, that there is a multitude of further constraints on these numbers, generalizing the Pauli principle. Here, we provide the first analytic analysis of the physical relevance of these constraints. We compute the natural occupation numbers for the ground states of a family of interacting fermions in a harmonic potential. Intriguingly, we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
192
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(198 citation statements)
references
References 18 publications
6
192
0
Order By: Relevance
“…Eigenvalues of 1-RDM are called natural occupation numbers. In general case, natural occupation numbers cannot be arbitrary ones within [0, 1] (simple Pauli's exclusion principle) and must satisfy generalized Pauli constraints [32][33][34][35].…”
Section: Spectra Of Particle-reduced Operatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eigenvalues of 1-RDM are called natural occupation numbers. In general case, natural occupation numbers cannot be arbitrary ones within [0, 1] (simple Pauli's exclusion principle) and must satisfy generalized Pauli constraints [32][33][34][35].…”
Section: Spectra Of Particle-reduced Operatorsmentioning
confidence: 99%
“…In quantum chemistry, a particle reduction is realized by integrating over irrelevant particles' coordinates [28][29][30], which results in the so-called p-particle reduced density matrix (see, e.g., [31]). Such an approach provides new inequalities for fermionic occupation numbers and leads to the generalized Pauli constraints [32][33][34][35]. As far as systems with a varying number of particles are concerned, the construction of p-particle reduced density matrices is non-trivial and we discuss it in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…The class of spin-compensated systems with time-reversal symmetry is a notable exception, since, in that case, the conditions for pure-state N -representability collapse to the ensemble conditions [32]. The necessary and sufficient conditions for pure-state N -representability, also called generalized Pauli constraints, have only recently been discussed and explicitly expressed for systems with a small number of particles and specific finite sizes of the Hilbert space [33][34][35][36][37][38][39]. Recently, it has been demonstrated that with enforcing only the ensemble conditions in a RDMFT calculation for open-shell systems, the pure-state conditions will be violated for many functionals of the 1RDM [40].…”
Section: Introductionmentioning
confidence: 99%
“…Because a d-dimensional 1-particle Hilbert space can be imbedded into any (larger) d 0 -dimensional one, one sees that the convex polytope P N;d is nothing but the intersection between P N;d 0 and the set of spectra with only d nonzero eigenvalues (see also Ref. [15]). Hence, any facet of P N;d arises from the intersection of some facet of P N;d 0 with the subspace of said spectra.…”
mentioning
confidence: 99%
“…Geometrically, these constraints define a convex polytope P N;d & R d of possible spectra (for more details see the Supplemental Material [15]). In general, if a spectral inequality such as (1) or (4) is (approximately) saturated, we say that the corresponding spectrum is (quasi)pinned to its extremum.…”
mentioning
confidence: 99%